Towards a theoretically motivated model for the lexicographic representation of Kinyarwanda phrasemes in General Kinyarwanda Dictionaries - Nikuze, Emmanuel (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.